Cessie, Subrogasi, dan Hawalah: Kajian Perbandingan Peralihan Hak dalam Hukum Perdata dan Hukum Islam: Cessie, Subrogation, and Hawalah: Comparative Study of Transfer of Rights in Civil Law and Islamic Law - Asisah, Siti Nur Asisah; Nuzulul Unsiyah; Ach. Iskandar Daul Kurnain; Nia Amelia; Ahmad Musadad (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The development of collateral law in Indonesia continues to undergo transformation to adapt to the dynamics of the national economy. This study aims to compare three mechanisms for the transfer of collection rights, namely cession, subrogation, and hawalah, from the perspective of civil law and Islamic law and analyze their implications for banking practices and financial transactions. This study uses a qualitative method of normative approach with comparative analysis, through a study of the Civil Code, Islamic legal literature, and related banking regulations. The results of the study indicate that cession is regulated in Article 613 of the Civil Code as the transfer of collection rights through an authentic deed or a private deed with notification to the debtor; subrogation is regulated in Article 1400 of the Civil Code as the transfer of creditor rights to a third party who pays off the debt; Meanwhile, hawalah in Islamic law is a transfer of debt based on sharia principles and is recognized in Islamic banking practices. The similarities between the three lie in the function of transferring collection rights, but differ in the legal basis, formal requirements, and underlying principles. The main focus of this research is to systematically compare the three mechanisms, namely cession, subrogation, and hawalah, in a comprehensive comparative analysis and examine their implications for banking practices and national financial regulations. Thus, this research is expected to enrich the academic literature in the fields of civil law and Islamic law and provide practical contributions to regulators and banking practitioners in formulating adaptive policies in accordance with sharia principles.